Determinants of Appropriate Complementary Feeding Practices among Mothers of Toddler - Dewi Rubi Fitriani; Maisharoh (Bulletin of Inspiring Developments and Achievements in Midwifery, 2026)
Timely and recommended complementary feeding (MPASI) is an important factor in preventing stunting and impaired growth and development in toddlers. However, the accuracy of complementary feeding in the working area of Andalas Health Center is still not optimal, influenced by low maternal knowledge, education level, and family support. This condition has the potential to increase the risk of nutritional problems in toddlers. This study purpose to analyze the determinants of appropriate complementary feeding practices among mothers of toddler. This study uses quantitative methods with a cross-sectional design. The population is all mothers who have toddlers aged 6–24 months, with a sample of 96 respondents selected through purposive sampling technique. The study was conducted in the working area of Andalas Padang Health Center. Data collection used structured questionnaires. Data analysis was conducted univariate to see the frequency distribution and bivariate using the chi-square test with a confidence level of 95% (α=0.05). The strength of the relationship was analyzed using the Contingency coefficient (C). Univariate results show that 62.5% of mothers provide proper complementary feeding, 70.8% have good knowledge, 58.3% have secondary-higher education, and 65.6% have good family support. The results of bivariate analysis showed a significant relationship between knowledge, education, and family support with the accuracy of complementary feeding. It was concluded that knowledge and family support had a strong relationship, while education had a moderate relationship. Operational implications highlight the need to optimize family-based nutrition education and counseling.